Do knee braces prevent ski knee injuries? - Negrin, R.; Uribe-Echevarria, B.; Reyes, N. (Asian Journal of Sports Medicine, 2017)
Background: Alpine skiing has high rates of knee injuries. Prophylactic knee braces (PKBs) and functional knee braces (FKBs) are often prescribed by clinicians to reduce injuries or re-injuries in skiers.